Responding to Climate Change in Tropical Countries Emerging from Armed Conflicts: Harnessing Climate Finance, Peacebuilding, and Sustainable Food - Castro Nuñez, Augusto (MDPI, 2018)
Linking climate action with sustainable development goals (SDGs) might incentivize social and political support to forest conservation. However, further examination of the conceptual entry points for linking efforts for reducing forest-based emissions with those for delivering SDGs is required. This review paper aims to contribute to fulfilling this research need. It provides insights into the links between conserving forests for climate change mitigation and peacebuilding. Specifically, the paper examines opportunities to harness climate finance for conserving forests and achieving long-lasting peace and sustainable food. It does so via a literature review and the examination of the Orinoquia region of Colombia. The findings from the literature review suggest that harnessing climate finance for conserving forests and peacebuilding is, in theory, viable if the activities are designed in accordance with social, institutional, and economic factors. Meanwhile, the Orinoquia region provides evidence that these two seemingly intractable problems are proposed to be solved together. At a time when efforts for reducing forest-based emissions are being designed and targeted at (post-) conflict areas in Colombia and elsewhere, the paper’s findings might demonstrate the compatibility of programs aimed at reducing forest-based emissions with efforts relating to peacebuilding and sustainable food to both environmental and non-environmental government agencies.